1998
DOI: 10.1128/cdli.5.5.622-626.1998
|View full text |Cite
|
Sign up to set email alerts
|

A Sensitive Method for Quantifying Cytomegalic Endothelial Cells in Peripheral Blood from Cytomegalovirus-Infected Patients

Abstract: A sensitive method has been developed for the quantification of cytomegalic endothelial cells (CEC) in peripheral blood (PB) of patients with active cytomegalovirus (CMV) infections. The three subsequent key steps of this method are density centrifugation to enrich endothelial cells (EC) in the mononuclear cell (MNC) fraction, EC-specific staining, and fluorescence-activated cell sorting (FACS) of EC onto adhesion slides. The FACS method was compared with the conventional method of cytocentrifugation of the MN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 33 publications
(37 reference statements)
0
3
0
Order By: Relevance
“…The detection of cytomegalic endothelial cells in peripheral blood of patients is another means of monitoring active CMV infection. Through enrichment of endothelial cells in the mononuclear fraction by density centrifugation, endothelial cell-specific staining, and fluorescence-activated cell sorting of these cells, a method with 10-fold greater sensitivity than cytocentrifugation of the mononuclear cell fraction alone has recently been developed for quantification of cytomegalic endothelial cells by FCM (158). Belles-Isles et al (24) have also suggested using FCM to monitor CMV infections by monitoring the CD8 ϩ CD38 ϩ T-cell subset in kidney transplant recipients; this T-cell subpopulation usually increases during active viral infections.…”
Section: Direct Detectionmentioning
confidence: 99%
“…The detection of cytomegalic endothelial cells in peripheral blood of patients is another means of monitoring active CMV infection. Through enrichment of endothelial cells in the mononuclear fraction by density centrifugation, endothelial cell-specific staining, and fluorescence-activated cell sorting of these cells, a method with 10-fold greater sensitivity than cytocentrifugation of the mononuclear cell fraction alone has recently been developed for quantification of cytomegalic endothelial cells by FCM (158). Belles-Isles et al (24) have also suggested using FCM to monitor CMV infections by monitoring the CD8 ϩ CD38 ϩ T-cell subset in kidney transplant recipients; this T-cell subpopulation usually increases during active viral infections.…”
Section: Direct Detectionmentioning
confidence: 99%
“…These cells can be identified by cytocentrifugation of the mononuclear fraction of leukocytes onto glass slides followed by endothelial cell-specific staining. A method for quantification of CEC in peripheral blood has also been described (220). In patients with AIDS, the detection of CEC is associated with lack of anti-CMV treatment, emergence of drug-resistant CMV, insufficient treatment, or transient response to antiviral therapy (152).…”
Section: Cytomegalic Endothelial Cellsmentioning
confidence: 99%
“…The incidence of infection can vary but in general 50-90% of the population is infected. In the healthy host, the acute phase of infection is self-limiting and the virus establishes a latent infection that can be reactivated in response to a variety of cellular stresses [5]. The long-term effects of viral persistence are the focus of many studies as HCMV infection has been implicated as a co-factor in the development of cardiovascular disease.…”
Section: Introductionmentioning
confidence: 99%